Marine phytoplankton composition and productivity in Talin Bay, Batangas - Fornillos, Editha P. (Animo Repository, 1988)
The phytoplankton of Talin Bay, Batangas, is represented by eighty-three species belonging to two phyla, two classes, three orders, fourteen families and twenty-seven genera. Correlation and stepwise regression show a significant relation between the productivity of the bay and parameters such as pH and salinity, time, temperature, silicate and nitrate. Chlorophyll a is positively correlated with salinity (0.341) at .05 level of significance and slightly correlated with temperature (0.205) and silicate (0.175). Dissolved oxygen is positively correlated with time (0.547) at .01 level of significance and slightly correlated with temperature (0.170) and pH (0.109). Biochemical oxygen demand is slightly correlated with pH (0.152) and orthophosphate (0.205) while net productivity is also slightly correlated with orthophosphate (0.203) and pH (0.154).Taxonomic keys and description of species were presented in this paper.